Profil Orang Tua Anak Autis (X) di SLB Autisma YPPA Padang - Yulia Kesra, Vegi; Fatmawati, Fatmawati (Inovan Publisher, 2024)
This research was motivated by a mother who has an autistic child who is currently undergoing individual therapy at SLB Autisma YPPA Padang. One of the therapies that is carried out is diet food therapy which is useful for reducing disorders of autism. At first, X's parents only made snacks for their children to eat, but after a request from the surrounding environment, X's parents were motivated to sell autism diet foods. This study aims to describe matters related to entrepreneurial motivation, how to process food, and strategies to sell diet food for autism. This research uses a case study method which is included in a qualitative approach. The subjects in this study were parents of autistic children X. The respondents in this study were the family (husband), the principal, and parents of autistic children who bought food from X. The data collection techniques used were observation, interviews, and documentation study. The results in this study reveal that parent X's entrepreneurial motivation in selling autistic diet foods is the encouragement that comes from within and from outside. In processing autistic diet food, parent X used ingredients, namely rice flour, sago flour, tilapia, jicama, pumpkin, green beans, garlic, himalayan salt, coriander, and oil with two filters. Meanwhile, the cooking utensils used are all made from glass and wood. The cooking techniques used are frying, boiling and roasting. The strategy of selling food by utilizing the knowledge and creativity he had, X's parents were able to attract consumers to buy the food he sold. It can be concluded that the profile of parents of children with autism X in SLB autism YPPA Padang is selling food in the form of snacks that are safe for consumption by children with autism.